MAKNA UPACARA PERKAWINAN SHINTO DI JEPANG - Helen Susanti (Universitas Pakuan, 2020)
A marriage ceremony is composed of rituals that are full of meaning, also decorated with clothes that are only worn at the time of marriage. This research analyzes the meaning of each ritual and dress in Shinto wedding ceremonies using Roland Barthes's Semiotic theory. Examine the connotation behind each ritual and clothing. All the rituals in the Shinto wedding ceremony have meaning as an announcement to God, relatives and friends of the bride and groom. While clothes have the meaning of showing the identity of the wearer. Keywords : Marriage, ritual, semiotic, Shinto